If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x + 3(3x + -4) = 21 Reorder the terms: 2x + 3(-4 + 3x) = 21 2x + (-4 * 3 + 3x * 3) = 21 2x + (-12 + 9x) = 21 Reorder the terms: -12 + 2x + 9x = 21 Combine like terms: 2x + 9x = 11x -12 + 11x = 21 Solving -12 + 11x = 21 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '12' to each side of the equation. -12 + 12 + 11x = 21 + 12 Combine like terms: -12 + 12 = 0 0 + 11x = 21 + 12 11x = 21 + 12 Combine like terms: 21 + 12 = 33 11x = 33 Divide each side by '11'. x = 3 Simplifying x = 3
| -2p+5p=3-21 | | X(2x-4)=(2x+8)(x-8) | | 56t^2-23t-63=0 | | 5(4-x)=-10 | | s^3+16s^2+64s=0 | | 6x^2+35x+25= | | 3x(a-3)-5(3-a)=0 | | 7x+3=-36 | | (x)(3x-y)(4x+5y)= | | 3x+7=-36 | | 8x-5=7-4x | | x/3-4=7 | | x(3x-y)(4x+5y)= | | -17+11+6=7t | | 2x+8=-48 | | 7xy^4-7xy^2=0 | | 3n^2-3n-36=0 | | 5(5x+3)=3(8x-2+4) | | x(3x-y)(4x+5x)= | | -7+11+6=7t | | 2x+25=-2x-7 | | 6(x-2)=14 | | 3x-39=75 | | 5=7t | | -4x+(-2x+6)=9 | | 13x+23=2x-13 | | -3x-8=x+16 | | -6x+2(x+6)=42 | | k-5k=-40 | | -3x-19=5+x | | -3x-19=5+5 | | 2x-1/4=5 |